Carboprost versus oxytocin for active management of third stage of labour - Ambika S. Patil; Vibhavaree Dadavate; Vidya A. Thobbi (Al Ameen Medical College, 2016)
Background and Objectives: Postpartum haemorrhage is a single largest and leading cause of maternal morbidity and mortality not only in developing countries but also in developed countries. Every 4 minutes one women die from pregnancy or child birth related complications. The present study is an attempt to evaluate the scope of using prophylactic intramuscular carboprost tromethamine 125μg in comparision with intramuscular oxytocin 10U for the active management of third stage of labour. Materials and Methods: Two hundred pregnant women at term with spontaneous onset of labour were included in the study and were randomly divided into 2 groups of 100 women each. Group A and Group B were given Inj.Oxytocin 10 units and Inj. carboprost tromethamine 125 ug intramuscular respectively at the time of delivery of anterior shoulder. The main outcome measures with respect to third stage of labour were: duration, blood loss by volume, difference in hemoglobin, need for additional oxytocics and side effects. Results: Carboprost tromethamine group had a significant reduction in duration of third stage (p < 0.05) and blood loss (p <0.0001) when compared to oxytocin group. Conclusion: Intramuscular carboprost is better alternative to intramuscular oxytocin in active management of third stage of labour.